2010
DOI: 10.1002/acr.20269
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil: A possible therapeutic agent for children with juvenile dermatomyositis

Abstract: Objective. To determine if mycophenolate mofetil (MMF) diminishes skin and muscle disease activity in children with juvenile dermatomyositis (DM), thereby permitting a decrease in corticosteroid dose. Methods. A retrospective data review for 50 children with juvenile DM (mean ؎ SD age 12.2 ؎ 5.0 years) who had received MMF for 12 months identified the following characteristics: 38 (76%) were girls, 39 (78%) were white, 10 (20%) were Hispanic, and 1 (2%) was African American. The MMF dose and frequency, type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 38 publications
0
41
0
3
Order By: Relevance
“…A retrospective review of 50 JDM patients treated with MMF for 12 months showed significant improvement in the validated disease activity scores for skin and muscle, as well as a decrease in mean prednisone dosage [19]. The infection rate 12 months before and after drug initiation was assessed in a subset of 26 children with JDM and showed no signs of increasing with use of MMF.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 97%
“…A retrospective review of 50 JDM patients treated with MMF for 12 months showed significant improvement in the validated disease activity scores for skin and muscle, as well as a decrease in mean prednisone dosage [19]. The infection rate 12 months before and after drug initiation was assessed in a subset of 26 children with JDM and showed no signs of increasing with use of MMF.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 97%
“…In a retrospective trial of 50 children with JDM treated with mycophenolate mofetil, Disease Activity Score improved and prednisone dose was decreased after 12 months [46]. Systemic tacrolimus therapy was shown to improve refractory skin disease as well as overall disease activity in a case series of three children with JDM [47].…”
Section: Other Agentsmentioning
confidence: 97%
“…Two retrospective studies where 12 [73] and 50 [74] JDM patients were treated with MMF demonstrated a good response and safety profile. It is usually given at starting dose of 600mg/m 2 /day, then can be increased to 1200mg/m 2 /day divided in two doses if well tolerated.…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%